2004
DOI: 10.1111/j.1439-0264.2004.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

An Immunohistochemical Study of Gastrointestinal Endocrine Cells in the BALB/c Mouse

Abstract: The distributions and frequencies of some endocrine cells in the eight portions of the gastrointestinal tract (GIT) of BALB/c mouse were studied. Endocrine cells were stained using immunohistochemical method with seven types of antisera against bovine chromogranin (BCG), serotonin, gastrin, cholecystokinin (CCK)-8, somatostatin, glucagon and human pancreatic polypeptide (HPP), and the regional distributions and their relative frequencies were observed in the eight portions of the GIT of BALB/c mice. All seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
6
1
Order By: Relevance
“…It is well known that somatostatin-IR cells have the widest distribution throughout the GI tract, except for the large intestine, among all vertebrate species examined using serotonin-IR cells [11]. However, somatostatin-IR cells were not detected in this study; this finding may be a strain-specific characteristic of Balb/c mice [10]. …”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…It is well known that somatostatin-IR cells have the widest distribution throughout the GI tract, except for the large intestine, among all vertebrate species examined using serotonin-IR cells [11]. However, somatostatin-IR cells were not detected in this study; this finding may be a strain-specific characteristic of Balb/c mice [10]. …”
Section: Discussioncontrasting
confidence: 55%
“…There has been extensive research on gastrointestinal (GI) endocrine cells in mouse strains, including normal Balb/c mice [3,10-12]. Changes in GI endocrine cells with some diseases have been demonstrated [1,5,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…EC cells are the best characterized subset of gut endocrine cells, which are dispersed throughout the gut mucosa and are the main source of 5-HT in the gut. [3][4][5] 5-HT can also be produced by mast cells in rodents, which are also increased in inflammation. 6 EC cells produce about 95% of 5-HT in the body and respond to luminal stimuli directly via the enzymes and transporters present on the apical part and indirectly by mediators from the surrounding cells.…”
Section: Background and Aimsmentioning
confidence: 99%
“…Several studies have demonstrated the regional distributions and relative frequencies of different endocrine cells in the gastrointestinal tract of various vertebrates, including several species and some of rodent species, and different kinds of these cells were described using immunohistochemical methods. In the Rodentia, the localizations of endocrine cells in the gastrointestinal tract of the rat (Sakata et al 2002;Sarı et al 2007), mice (Sandstrom & El-Salhy 2000), gerbil (Lee et al 2000), hairless mouse (Ku et al 2002), C57BL/6 mouse (Ku et al 2003), Balb/c mouse (Ku et al 2004a), ddY mouse (Ku et al 2004b), nude mice (Ku et al 2006) and ddN mice (Lee et al 2010) were demonstrated. Changes of regional distribution and relative frequency of some gastrointestinal endocrine cells with aging were also reported in mice (Sandstrom & El-Salhy 2000) and the distribution and frequency of gastrointestinal endocrine cells in various mouse species has been shown with strain-dependent differences to a certain degree (Ku et al 2002(Ku et al , 2003(Ku et al , 2004a(Ku et al , 2004b.…”
Section: Introductionmentioning
confidence: 99%